From Traditional to Modern: Evolving Practices in Language Testing and Assessment (Interdisciplinary Research in Education, 2024)
This paper looks into the shifts from traditional to innovative and inclusive language testing methods, focusing on developments such as alternative assessment, AI integration, and computer-adaptive testing. This study employs a desk-based approach to the literature which synthesizes relevant theories in order to highlight the increased focus on fairness, inclusivity and authentic assessment. The key findings highlight that dynamic and performance-based assessments address the different learning needs of the learners; promote instrumentality towards language use and incorporate socio-political and ethical dimensions in test construction. The paper also underlines the transformative power of technology to improve access and efficiency considering the potential challenges and inequalities associated with its use. By integrating traditional and modern practices, this study contributes to both the theoretical discourse and practical advancements in language assessment that uphold equitable, ethical and effective testing methods consistent with twenty-first century educational standards and learner diversity.